Leadership Model in Integrated Islamic Educational Institutions - Makruf, Imam (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
Leadership has an important role in educational institutions. The increasing number of implementation models of integrative Islamic education institutions demand greater competence of the leaders in order to perform their duties effectively. The most complex integrative Islamic educational institution model is developed based onboarding school by integrating formal and nonformal education as well as a cross ladder as developed by Al Mukmin Islamic Boarding School (PPIM) Ngruki and modern boarding schools in general. The result of this study shows that the effective leadership model of an integrative Islamic educational institution is a democratic-transformational model. This model needs institutional leaders to have professional, personal, social, and spiritual competences. The integration of the educational institution's management should be done thoroughly starting from the integration of curriculum management, human resources, infrastructure, financing, public relations and marketing, and other aspects.